DEVELOPMENT OF COMPULSORY INSURANCE TYPES - Matiyazova S.R. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The importance and nature of compulsory insurance is explained in the article, and the mandatory procedure is given in it.